2021
DOI: 10.1016/j.jamda.2021.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses After mRNA-Based COVID-19 Vaccination in Residential Older Adults: Implications for Reopening

Abstract: Objective COVID-19 disproportionately impacts residents in long-term care facilities. Our objective was to quantify the presence and magnitude of antibody response in vaccinated, older adult residents at assisted living, personal care, and independent living communities. Design A cross-sectional quality improvement study was conducted March 15 – April 1, 2021 in the greater Pittsburgh region. Setting and Population: Participants were older ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…These data align with recent observations of decreased antibody production and/or neutralization after BNT162b2 vaccination in nursing home residents compared with healthy young individuals. 4 , 5 , 6 In addition, we found that vaccination against SARS-CoV-2 with mRNA-1273 elicited a stronger humoral response compared with BNT162b2, with greater circulating IgG and neutralization antibody titers ∼3 months after vaccination. The mRNA-1273 vaccine contains a higher dose of mRNA, which may imply that a higher dose is beneficial to generate protective immunity in nursing home residents.…”
Section: Discussionmentioning
confidence: 73%
“…These data align with recent observations of decreased antibody production and/or neutralization after BNT162b2 vaccination in nursing home residents compared with healthy young individuals. 4 , 5 , 6 In addition, we found that vaccination against SARS-CoV-2 with mRNA-1273 elicited a stronger humoral response compared with BNT162b2, with greater circulating IgG and neutralization antibody titers ∼3 months after vaccination. The mRNA-1273 vaccine contains a higher dose of mRNA, which may imply that a higher dose is beneficial to generate protective immunity in nursing home residents.…”
Section: Discussionmentioning
confidence: 73%
“…The potential effect of corticosteroid use on the immunogenicity of COVID-19 vaccines has not been thoroughly investigated. There was a report that the antibody level was lower in a low-dose steroid user in an older adult cohort who received two doses of mRNA vaccine, but the sample size was small and statistical significance was not achieved (24). It also was reported that the immunogenicity of COVID-19 vaccines in solid organ transplant recipients was poor, but they took T-cell suppressive agents in addition to corticosteroids (9,25).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid and robust IgG response may suggest that S protein, used in the BNT162B2 vaccine, is highly immunogenic. Effective immunogenicity was observed in LTCF residents also in other COVID-19 vaccines (Nace et al 2021 ). Another argument for a vaccination of COVID-19 recovered individuals are observations that a single dose of mRNA vaccine boosted neutralising titers also against other variants of the virus (Stamatatos et al 2021 ).…”
Section: Discussionmentioning
confidence: 92%